Assessing Soil Nutrient and Biomass Contributions to Peatland Formation - Armanto, M. Edi; Wildayana, Elisa; Imanudin, Momon Sodik (PLANTA TROPIKA, 2025)
Peat formation is the main key to carbon sequestration in the Peat Swamp Forest (PSF). The research aims to analyze alternative possibilities for peat formation based on the available soil nutrients and dried biomass. In a complete randomized block design, a factorial trial was applied using two treatment combinations in three blocks: factor A (sampling plots, land cover) and Factor B (dried biomass). Data were analyzed using two-way ANOVA and Tukey Honestly Significant Difference test at a significance level of 5%. A high supply of dried below-ground biomass did not follow the production of rooting litter at high soil nutrients. Most of the biomass was transported upwards into above-ground biomass. All land covers produced above-ground biomass which had the potential to form peat with significant differences for all parameters studied. The potential for peat formation was highly dependent on the various types of land covers (e.g. peat forest), environmental factors, the composition of the seed bank, and the species ability to compete. Restoration actions (revegetation, rewetting, and revitalization) aim to stimulate the development of peat-forming species. The research benefits are expected to enrich PSF's ecological restoration thinking so that PSF can be restored and returned to near its initial condition.